From Skills to Agency: CBO Education Intervention and Women’s Economic Empowerment in Montserrado County - Tolbert Thomas Jallah, Jr. (International Journal on Economics, Finance and Sustainable Development, 2026)
Women in Montserrado face structural barriers that limit the translation of CBO training into income, asset control, and household decision-making, and existing evaluations rarely identify ineffective interventions. This study assessed the impact of CBO education interventions on women’s economic empowerment using the Capability Approach and a mixed-methods convergent parallel design. It targeted a total of 42,990 women comprised of the beneficiaries of the program. The sample borrowed Kothari’s formulae in arriving at 384. This sample was distributed proportionally across five districts. Out of the 384 who were initially targeted, 310 returned the questionnaires duly filled. The analysis first took a quantitative angle; this entailed the use of descriptive analysis as well as correlations and cross-tabulations coupled with ANOVA and multiple regressions. On the other hand, qualitative analysis was also done. This involved the data that was collected in terms of interviews, FGDs. This data was paraded thematically and analyzed. Results from the cross tabulation revealed that women received marginal gains in formal education (25% vs 11.8%), digital literacy (25% vs 8.3%), and vocational training (21.1% vs 11.1%), with inconsistent informal education effects (14%). Correlations were weak (r = –0.10 to 0.07), regressions showed negligible predictive effects (digital literacy β = –0.144, informal education β = –0.091), and ANOVA results were non-significant (F = 0.98–1.72, p > 0.16). Qualitative insights highlighted persistent constraints, including limited capital, market access, household barriers, and poor infrastructure. The results of the study indicated that education through CBO alone is not enough to bring about significant economic empowerment unless it is accompanied by economic and social support.